(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2023)
Purpose: A study was made of the effects of some bases and adjuvants on the physical and release properties of metronidazole suppositories with a view to providing more information for the optimization of the rectal formulation of metronidazole.Method: Suppositories (1g) containing 200mg of metronidazole each were prepared in witepsol (H15 and E75) and polyethylene glycol (PEG 2850 and 4650) bases, using different concentrations of Tween 80, sodium salicylate and methylcellulose as adjuvants. The setting time, solidification point and melting range of the suppositories were determined, along with their crushing strength, disintegration time and the time for 80% of metronidazole to be released from the suppositories (t80).Results: The ranking of setting time for the suppositories was witepsol H15 > PEG 2850 > witepsol E75 > PEG 4650, while the ranking of solidification point, melting range, crushing strength, disintegration time and the time for 80% of metronidazole to be released from the suppositories (t80) was the reverse of that for setting time. Optimal concentrations of Tween 80 and sodium salicylate were observed for the suppository formulations. Using Kitazawa plots, all formulations showed two dissolution rate constants, k1 and k2 intersecting at time t1, with formulations containing 5 to 20 % w/w of methylcellulose exhibiting a third dissolution rate constant, k3 intersecting with k2 at time t2.Conclusion: The physical and release properties of metronidazole suppositories are influenced considerably by the bases and adjuvants employed. Tween 80 and sodium salicylate can probably be used to formulate only immediate-release suppositories while methylcellulose can be useful for sustained-release metronidazole suppositories. Some insight into these inferences can be obtained from parameters derived from Kitazawa plots.